Intensive care experience among intensive care unit survivors - Mohamed Ariffin, Suzilawati; Pinyokham, Nitaya; Tachaudomdach, Chiraporn (2016)
Introduction: Critically ill patients need advanced support to remain alive and prevent serious complications. However, patients may experience either pleasant or unpleasant memories during their stay in Intensive Care Unit (ICU). Unpleasant experiences can affect patients or lead to later negative consequences. Critical care nurses have a pivotal role in identifying traumatic experiences in order to improve care.